LAS MINORÍAS SEXUALES EN EL CINE DOCUMENTAL ARGENTINO RECIENTE - Dr. Pablo LANZA (Fonseca, Journal of Communication, 2023)
Argentine cinema consigned to a marginal place the representation of dissident sexualities during most of its history. From the first years of the 21st century, these stories began to take center stage in multiple films, especially within the documentary genre. This change took place in parallel to the struggles for civil rights undertaken by multiple groups and associations, initiated with the first Pride March in 1992 and culminating with the approval of the Gender Identity Law in 2012